Prosedur Pembuatan Pollo Funghi Pizza Di Kitchen Restoran K Resto - Rupminiasih, Ni Nyoman; Polikarpus Nainggolan, Pondang; Sandi Artha Putra, I Nengah (Universitas Triatma Mulya, 2024)
Pollo Funghi Pizza is a type of pizza topped with tomato sauce, cheese, mushrooms and chicken. This research was conducted to find out the procedure for making pollo funghi pizza at Kitchen K restaurant. There are three problem formulations contained in this research, namely what is the procedure for making pollo funghi pizza at K restaurant, what are the obstacles that often occur in making pollo funghi pizza at K restaurant, efforts that can be made to overcome obstacles in making pollo funghi pizza at K restaurant. The theory in this research discusses tourism, hotels, kitchens, procedures, cooking and cooking methods. The data analysis technique used is descriptive qualitative, where the research produces descriptive data that describes, depicts, explains, explains and answers in more detail the problems to be studied. The data collection methods used were observation, interviews and documentation. The results of this research show that the procedure for making pollo funghi pizza is quite good, the taste and quality of the pizza produced has received good feedback from guests, and pollo funghi pizza has become one of the favorite pizzas. In making pollo funghi pizza there are obstacles, namely pizza dough that is tight or less elastic, running out of stock of ingredients and equipment damage